INDIGENOUS IDENTITY AND ORIENTALISM: A CRITICAL STUDY OF BLACK SKIN, WHITE MASKS IN THE CONTEXT OF COLONIALISM AND DIASPORA (Forum for Linguistic Studies, 2024)
Abstract:  Communication plays a vital role in all aspects of life. Language serves as a universal tool for effective communication. Throughout history, the significance, influence, and impact of language in communication have been evident across different stages and levels. The language was notably used as a dominant tool by colonizers to establish and enforce their power over the colonized populations. Numerous postcolonial discourses have addressed the influential role of language during the era of colonization. The language of the European colonizers was often regarded as a means of suppressing, oppressing, marginalizing, and discriminating against race, class, gender, culture, and identity. This research paper specifically examines the impact of language on Indigenous culture in Africa, as portrayed in Frantz Fanon's novel, Black Skin, White Masks.